Effective Application of Nanocarriers in Cosmetic Formulation Iteration and Upgrading - Wu, Ruofei (Transactions on Environment, Energy and Earth Sciences, 2026)
This study aims to systematically explore the role and application value of nanocarriers in cosmetics. Through a review and analysis of common types of nanocarriers and their mechanisms of action, combined with previous experimental data, their performance advantages in the delivery of active ingredients in cosmetics were evaluated. The investigation found that organic carriers such as liposomes, solid lipid nanoparticles (SLNs), and nanoemulsions have shown significant effects in improving component stability, permeability, and controlled release; Inorganic nanoparticles such as titanium dioxide and zinc oxide can achieve efficient UV shielding in sunscreen, while gold and silver nanoparticles have both antioxidant and antibacterial effects. Application surveys have shown that nanocarriers have significant effects in sun protection, anti-aging, moisturizing, restoration, and oral care scenarios. However, research also points out challenges in terms of uncontrollable skin penetration, potential toxicity accumulation in the body, insufficient targeting, and risk of degradation by-products. Therefore, this study believes that nanocarriers have great potential in optimizing the efficacy of cosmetics, but in the future, it is necessary to strengthen safety assessment, material degradability, and precise targeting technology research and development to achieve a balance between efficacy and safety.
Keywords: Nanocarrier; cosmetics; cosmetic efficacy.